A C-terminal encoded peptide, ZmCEP1, is essential for kernel development in maize. (9th June 2021) - Xu, Ruibin; Li, Yufeng; Sui, Zhipeng; Lan, Tianyu; Song, Wanjun; Zhang, Ming; Zhang, Yirong; Xing, Jiewen
Abstract: C-terminal encoded peptides (CEPs) are peptide hormones which act as mobile signals coordinating important developmental programs. Previous studies have unraveled that CEPs are able to regulate plant growth and abiotic stress via cell-to-cell communication in Arabidopsis and rice; however, little is known about their roles in maize. Here, we examined the spatiotemporal expression pattern of ZmCEP1 and showed that ZmCEP1 is highly expressed in young ears and tassels of maize, particularly in the vascular bundles of ears. Heterologous expression of ZmCEP1 in Arabidopsis results in smaller plants and seed size. Similarly, overexpression of ZmCEP1 in maize decreased the plant and ear height, ear length, kernel size, and 100-kernel weight. Consistently, exogenous application of the synthesized ZmCEP1 peptide to the roots of Arabidopsis and maize inhibited root elongation. Knock-out of ZmCEP1 through CRISPR/Cas9 significantly increased plant and ear height, kernel size and 100-kernel weight. Transcriptome analysis revealed that knock-out of ZmCEP1 up-regulated a subset of genes involved in nitrogen metabolism, nitrate transport, sugar transport and auxin response. Thus, these results provide new insights into the genetic and molecular function of ZmCEP1 in regulating kernel development and plant growth, providing novel opportunities for maize breeding. Abstract : ZmCEP1 functions to affect plant height and kernel size in maize, and has a potential role in nitrogen metabolism, sugar transport and auxin response.